Relations between the occurrence of hypermobility and gender in the group of children aged 6 - 10 years - Maryczkanicz, Joanna; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2018)
Introduction:Hypermobility of joints in healthy people may be either acquired or congenital be a symptom of a connective tissue disorder such as Marfan syndrome, osteogenesis imperfecta, or Ehler-Danlos syndrome. If that occurs increased joint mobility does not have the characteristics previously mentioned teams innate, it may indicate the presence of articular hypermobility. Hypermobility otherwise called excessive joint laxity or increased their chattel. This dysfunction is based on a wider range of movement in large and small joints relative to the standards for age, gender and race, in the absence of rheumatic diseases. The aim of the study was to evaluate the relationship between hypermobility and gender of the children aged 6 - 10 years. Materials and Methods: The study was conducted in November and December 2017, in two primary schools in Szczecin. Studied 66 children, whose average age was 7 years and 10 months. To assess the prevalence of hypermobility used Beighton scale. It consists of preparation of 5 steps: slope forward from the position the hand flat on the floor, the passive hyperextension V above the finger 90, the passive thumb adduction to the volar side of the forearm hyperextension elbow joint and knee joint. The maximum number of points available is a ninth score 4 points or more indicates presence of hypermobility. Results: The results of 4 points or above on a scale Beighton was observed in 24 of 66 children. Boys was 10, and girls 14. Among girls male person with hypermobility accounted for 30.30%, and among female patients with hypermobility was 42.42% . Conclusions: There was an increased incidence of joint mobility of females than males. The need for screening tests in that group of children was also highlighted.